Laparoscopic portosystemic shunt attenuation in 20 dogs (2018‐2021). (22nd February 2022) - Poggi, Edoardo; Rubio, David Garcia; Pérez Duarte, Francisco J.; del Sol, Jorge Gutiérrez; Borghetti, Luciano; Izzo, Francesca; Cinti, Filippo
Abstract: Objective: To describe the technique, complications, and outcome of laparoscopic portosystemic shunt attenuation (LPSSA) in dogs. Study design: Retrospective study. Animals: Twenty client‐owned dogs. Methods: Medical records were searched for dogs with a single congenital extrahepatic portosystemic shunt (CEPSS) that was treated with LPSSA. Signalment, clinical signs, CEPSS location, diagnostic imaging, laparoscopic approach, operative technique, complications, and clinical outcome were reviewed. Results: Fourteen dogs with CEPSS located in the epiploic foramen had a right (13/14) or left (1/14) paramedian approach. In 6 dogs a CEPSS was not located in the epiploic foramen, and a left paramedian approach was used. A 3 or 4‐port technique was used in 7 and 13 dogs, respectively. A thin film band was used for CEPSS attenuation in all dogs. The median operating time for LPSSA was 62 min (range 27‐98 min). Intraoperative complications requiring conversion to an open technique occurred in 5 dogs. Mild perioperative self‐limiting portal hypertension occurred in 3 dogs, while severe portal hypertension with surgical revision occurred in 1 case. The complications were resolved, and all dogs had a good outcome. Conclusion: Laparoscopic portosystemic shunt attenuation can be performed in dogs, in particular for a CEPSS located in the epiploic foramen using a right paramedian approach. For CEPSS not located in the epiploic foramen, a left paramedian approach is recommended. Conversion to open celiotomy was required in around a third of cases. Clinical significance: Laparoscopic attenuation of CEPSSs can be performed in dogs and has a good clinical outcome, particularly for CEPSS located in the epiploic foramen.